Elmer and the tune [anglicky] - McKee, David (London : Andersen Press, 2018)
When Rose meets Elmer she's humming a tune, a tune she just can't get out of her head. When she leaves, Elmer realises he can't get the tune out of his head either and as he crosses the jungle he can see the infectious tune spreading to every animal Rose has met! Can Elmer help everyone get rid of it?
Originally published: 2017.
Keywords: Elmer -- (Fictitious character from McKee) -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works; čítame si spolu 0+; cudzojazyčná literatúra